(NnEZABUDKI DLQ aN@TKI (B/s - (NwASKAN(B, (NwASILX wASILXOWI^(B.s; (NwUDWUD(B, (Nk(B.s ((NkATERINA(B)s ((N~ERN)QÆWCÆ (B:s)E (NrODOW)QÆD(B,s)E, 2023)
(NcQ DITQ^A KNIVE^KA BULA NAZWANA (B"(NnEZABUDKI DLQ aN@TKI(B" (NW DENX NARODVENNQ PRAWNU^KI AWTOR)QÆ aNNI(B. (NnEZABUDKI(B, (NABO BRATKI (B- (NCE KWÆTI VITTQ(B. (NwÆR[Æ(B-(NNEZABUDKI(B, (NQK MALENXKÆ NAGADUWANNQ MALIM PRO WELIKE(B, (NWAVLIMWE(B, (NPOWSQKDENNE Æ WS@DISU]E(B, (NPOTRÆBNE W VITTÆ(B.s)E
(NgOLOWN)QÆJ kNIGOSKRINÆ kRA@ (B- (NbÆBLÆOTECÆ ÆM(B. (Nm(B. æ(NWAS@KA NA sLAWU uKRAÇNI WÆD AWTORÆW(B. 03.10.23.s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NuKRA)QÇNSXKAs)E -- (NpOEZ)QÆQ(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E